Characteristics of undergraduate dental theses defended in Peruvian licensed universities and factors associated with their publication - Cossio-Alva, Bryan Alexis; Corrales-Reyes, Ibraín Enrique; Pares-Ballasco, Giancarlo; Luna-Mazzola, Ivo; Sánchez-Ormeño, José; Laura-Lopez, Nievesrosa; Villegas-Maestre, José Daniel; Mejia, Christian R. (Frontiers in Education, 2023)
In order to characterize the dental theses defended in licensed Peruvian universities, as well as to identify the factors that favor their publication in scientific journals, a cross-sectional, analytical and observational study was conducted using a search strategy in Google Scholar. We ascertained whether the theses defended between 2015-2018 had been published in scientific journals. Prevalence ratios (aPR), 95% confidence intervals (CI 95%) and p-values were obtained using generalized linear models. Most of the theses were defended in private universities (65.9%), located in the provinces (76.7%), in 2017 (32.1%). The most studied line of research was Dental Education (n=418; 18.4%). Of the total number of defended theses (n=2267), only 130 (5.7%) were published, in a total of 41 scientific journals, of which 22 are specialized in the dental field. The 130 articles received 443 citations, with an average of 3.4 citations per document. The Universidad Católica Santa María was the institution that defended the most theses (n=372); however, the Universidad Científica del Sur presented the highest percentage of published theses (36.4%). Theses with case-control (aPR: 2.74; CI 95%: 1.07-7.01; p=0.036) and cohort (aPR: 3.51; CI 95%: 2.02-6.11; p<0,001) methodological design had a higher frequency of publication; on the contrary, those executed in the community were less frequently published (aPR: 0.39; CI 95%: 0.17-0.93; p=0.033), as well as, those with two researchers (aPR: 0.41; CI 95%: 0.18-0.92; p=0.031), adjusted for two variables. Only one in twenty theses was published. Publication was associated with the type of methodological design, the place of execution and the number of researchers.